Peningkatan Kompetensi Lulusan SMK Taruna Karya 1 Karawang dalam Bidang Jaringan Transmisi Fiber Optik guna Memenuhi Standar Kompetensi sesuai SKKNI - Lela Nurpulaela; Arnisa Stefanie; Ridwan Satrio Hadikusuma; Dedi Pahroji (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Covid-19 pandemic, which has been around for more than a year, has limited aspects of life, one of which is education. The learning process that should be carried out face-to-face, then switches to online or face-to-face. The PKM (Community Service) activity "Improving the Competency of Graduates of SMK Taruna Karya 1 Karawang in the field of Fiber Optic Transmission networks in order to meet Competency Standards according to SKKNI" involves school partners of the Karawang Regency Vocational School. Fiber optic cable has many advantages in distributing data. So it is necessary to conduct lessons and workshops on the use of fiber optic cables using DWDM technology. In this activity, partners will be given workshops on fiber optic cables, various theories about fiber optic cables and learning modules that are compiled and adapted based on SKKNI standards in fiber optic installations as learning media with the self learning method, because fiber optic cables are very different from copper cables. In general, the purpose of this service is: 1) Providing knowledge to students of SMK Taruna Karya 1 Karawang about Fiber Optic, 2) students can be more familiar with fiber optics, 3) TKJ students of SMK Taruna Karya 1 Karawang have Fiber Optic competence. The method in this community service activity is carried out by holding learning and providing teaching materials for learning with the self-learning method